Application of the AHP Method to Assesment of Performance Levels of Production Employees of the Zenbo Division of PT. ABC: Penerapan Metode AHP terhadap Penilaian Tingkat Kinerja Karyawan Produksi Divisi Zenbo PT. ABC - Prasetyo, Doni Prasetyo; Marodiyah, Inggit (Universitas Muhammadiyah Sidoarjo, 2024)
In a company, it cannot be separated from the role of human resources who work in it. The quality of human resources is one of the factors that influences the level of company productivity. Therefore, there is a need for an existing employee performance assessment system to determine the level of productivity of each existing employee. The problems that exist at PT. Mertex Indonesia is the absence of an assessment system which results in no knowledge of the performance level of its employees. Based on these problems, this research designed an employee assessment system using the Analytical Hierarchy Process (AHP) method which is used to support decision making for employees which refers to the employee's level of productivity. This research aims to create decision support in evaluating the performance of company employees to be able to maintain the high value of company productivity. The results obtained from weighting using AHP are changes in ranking where operator 2 and operator 3 exchange ranking positions. Highlights : Lack of performance assessment system at PT. ABC impacts productivity. Research designs AHP-based employee assessment system. Results show ranking changes, enhancing decision-making for productivity. Keywords : Human Resources; AHP Method; Performance Assessment